Castle: The complete seventh season The complete seventh season. - Marlowe, Andrew W.; Fillion, Nathan, 1971-; Katic, Stana; Dever, Seamus, 1976-; Huertas, Jon; ABC Studios (Burbank, California : ABC Studios, 2015)
The wedding bells are ringing, but will Castle and Beckett really tie the knot? On the biggest day of his life, Castle is nowhere to be found, and it2s not because he has cold feet. Now, in a season of brilliant twists and turns, Castle and Beckett take on New York City2s most fascinating cases while they try to solve the mystery of their own relationship.
Title from sell sheet.
Originally broadcast as episodes of the television program in 2014.
16x9 widescreen (1.78:1).
Bonus features: audio commentary; Raging heat webmercial; deleted scenes; "Definition of love" performed by Shay-Jean; the cast behind the cast; bloopers.
new dvd 2022 fall.
Creator, Andrew W. Marlowe.
Keywords: Novelists -- Drama; Women detectives -- Drama; Crime writing -- Drama; Criminal investigation -- Drama; Fiction television programs; Video recordings for the hearing impaired; Drama; Crime television programs